Storage changes in pork pies - Milbourne, Karen (1984)
This research project was designed to investigate the chemical and physical changes in pork pies during storage. Lipid oxidation and moisture migration were found to be the parameters of most importance, with protein cross-linkaging and colour changes in the meat filling "'having' less of a deteriorative effect on pie shelf life. The extent of lipid oxidation and the development of rancidity (taste and odour) were found to be affected by cooking, the age of the meat and back fat in the meat filling and by their storage conditions (temperature and time). An increase in all or any of these parameters was found to increase the rate of rancidity development. On the other hand the rusk and the seasoning mix used in the meat filling of the pies, were found to reduce the rate of rancidity development. This antioxidant activity was investigated further. In the rusk, substances produced by the maillard browning reaction during the course of its manufacture were found to be antioxidative. However prolonged heating, although it produced a rusk with high antioxidant activity, had lowered its water binding capacity sufficiently to prevent its use in the meat products where water has to be bound to an inert filler. The antioxidant component of the seasoning mix was found to be white pepper, with the ethanol soluble fraction exhibiting this activity. Lipid analyses showed that rancidity developed parallel to the loss of the unsaturated fatty acids which had a chain length of 16 or above carbon atoms; and a concomitant rise in the concentration of short chain fatty acids and aldehydes, especially those having five and six carbon atoms in the chain length. The level of hexanoic acid (C6: 0) rose as rancidity developed, being development most marked in the pies with the fastest rate of rancidity development (i. e. those devoid of both the rusk and the seasoning mix). Moistture migration, both from. the atmosphere and from the jelly into the pastry (especially into the brown outer layer of pastry) resulted in an increase in moisture content, and a decrease in texture, of the pastry. Threshold levels for these two parameters were established above and below which respectively the pastry was deemed unacceptable, and these values were used subsequently in the investigation to assess the effect of various products on shelf life extension. Simultaneous lowering of the relative humidity (r. h. ) of the external atmosphere, and lowering of the jelly aw to levels at which to prevent moisture migration into the pastry resulted in a 35 day shelf life for the pies. However the use of glycerol to reduce the jelly aw to 0.56 resulted in an unpleasant taste to the pie. Lowering the jelly aw to 0.84 gave an extension (of at least 2 days) to the usual 8 days shelf life. Unfortunately attempts to achieve this aw (0.84) by the use of binders and pfi, were unsuccessful. Similarly the use of cetyl alcohol as a moisture barrier within the pork pie was not effective. The formation of a gelatin-lactein cogel, showed excellent potential for reducing moisture migration in pork pies.